Test Driven Development in OWOW’s Full-stack Web Development - Albert Edwillian Pratomo; Erik van der Schriek; Thomas van der Veen (Institute of Research and Community Outreach - Petra Christian University, 2020)
OWOW is a digital agency which operates in the context of software development, design, and digital marketing. One of the key services it provides is full-stack web development. OWOW separates its full-stack web development into back-end and front-end. OWOW had done some automated testing in back-end, but none in front-end. This was not ideal because the quality of web apps developed could not be easily and thoroughly ensured. OWOW believes Test Driven Development (TDD) might be the solution for the situation. TDD is a software development process where test code are written before the implementation code. Through this project, OWOW would like to start applying TDD into its full-stack web development. Research had been done to investigate how to apply TDD in OWOW’s current workflow. In the research, the TDD approach was defined. Afterwards, its application on current back-end and front-end development was investigated. Furthermore, its relation to Continuous Integration was explored. The research findings were then implemented on an ongoing web project called RentIt. This implementation had been delivered as a proof-of-concept application of TDD in OWOW’s full-stack web development. It is concluded that OWOW had been introduced to apply TDD in its full-stack web development.